A new environmentally-friendly route to in situ form a high-corrosion-resistant nesquehonite film on pure magnesium. Issue 58 (25th September 2020) - Cao, Xianlong; Ren, Quanyou; Yang, Youkun; Hou, Xianglong; Yan, Yongbo; Hu, Jie; Deng, Hongda; Yu, Daliang; Lan, Wei; Pan, Fusheng
Abstract : A nesquehonite protective film with high corrosion resistance was prepared on pure Mg via a new environmentally-friendly in situ carbonation route. Abstract : Magnesium-based materials are promising lightweight structural materials due to their excellent properties. However, their extensive application has been severely limited due to their high corrosion susceptibility. The inadequate corrosion resistance of Mg is mainly attributed to the porous and unprotective native surface film formed on Mg in aggressive environments. Here, we demonstrated a new environment-friendly route for the growth of a continuous nesquehonite (MgCO3 ·3H2 O) protective film on the surface of pure Mg metal at a relatively low temperature via an in situ reaction of the Mg surface with gaseous phase CO2 in humid environments. The protective film consists solely of highly crystalline MgCO3 ·3H2 O that is compact and has an umbrella-like structure. Electrochemical tests showed that compared to the untreated Mg substrate, the protective film can effectively improve the corrosion resistance of the substrate by nearly two orders of magnitude. Additionally, a possible formation mechanism of the nesquehonite film on the pure Mg was proposed and the effect of the carbonation time on the film was investigated. This environmentally-friendly surface treatment method is promising for use in the protection of magnesium-based materials.